A experiência do luto vivida por um pastor evangélico - Carneiro, Keila Moreira (2024)
Grief is an experience lived after the loss of a significant bond. It takes place within a broad context that encompasses religion, for its supportive role, validation of grief, and provision of access to support networks. Religion is also a way of making sense of and seeking meaning to life and death through the expression of spirituality. Evangelicalism is the second-largest religious denomination in Brazil, accounting for 22.16% of the population, and its bereaved members can find solace within their religious communities and from their leaders. Religion has been studied for its role in providing support at times of grief, but the grief experienced by evangelical religious leaders has not been given the same investigative attention. However, the losses experienced by religious leaders can act as triggers of disenfranchised grief, thus representing a risk factor for complicated grief, which may contribute to impairments in physical and mental health among this group. The primary objective of the present investigation was to explore the experience of grief lived by an evangelical religious leader. Specific objectives included exploring his perception of his grief process, identifying the presence of unrecognized grief in this context, and contributing to the prevention of burnout syndrome among evangelical religious leaders. A qualitative case study was conducted employing semi-structured interviews as the data collection instrument. Data were analyzed using content analysis. The results of the analysis provided insights into the experience of grief lived by an evangelical religious leader and the implications for his relationships with God and religious representatives, family, and individuals within his socio-affective circle. The results also revealed the bereaved individual’s perception of the grief process, shedding light on the role of institutional support in the prevention of complicated grief and burnout syndrome. (This study was supported by the Fundação São Paulo – FUNDASP, São Paulo, Brazil.)